2022
DOI: 10.1186/s41155-022-00233-z
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, insomnia, and depression during COVID-19 lockdown in elite individual and team sport athletes

Abstract: Purpose Pandemic-induced lockdowns disrupted sport training and competition. We aimed to identify the impact on the mental health of high-level athletes and clarify whether the effects differ for team-based and individual athletes. Methods This cross-sectional survey, stratified by sex and sport type, collected demographic data and mental health measurements from 274 Brazilian high-performance athletes (142 from team sports and 132 from individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Individual athletes’ ability to experience positive emotions through the reappraisal of stressful situations can fight negative behavior in their case. However, according to Salles et al [ 37 ], the personality traits and the genetic predispositions of the athletes are also important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual athletes’ ability to experience positive emotions through the reappraisal of stressful situations can fight negative behavior in their case. However, according to Salles et al [ 37 ], the personality traits and the genetic predispositions of the athletes are also important.…”
Section: Resultsmentioning
confidence: 99%
“…According to the type of sport practiced, athletes reported different mental health issues during the lockdown. Team athletes reported more insomnia and depression symptoms than individual sport athletes, possibly as a result of new and unfamiliar social isolation and a lack of social team activity [ 36 , 37 ]. Individual athletes are more likely to develop psychological problems in typical conditions because performing well in individual sports requires a higher level of internal attribution and no opportunity to share responsibility with teammates [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of mental disorders has been on the rise in recent decades (ten Have et al, 2023), with children and young adults under 24 years of age being particularly affected by the adverse mental health effects of the COVID-19 pandemic (Kauhanen et al, 2023). While team sport athletes typically exhibit lower levels of anxiety and depression compared to individual sport athletes (Pluhar et al, 2019), the mental well-being of team sport athletes is susceptible to the impact of the COVID-19 pandemic due to the lack of social team activities (Salles et al, 2022). Consequently, exercise modalities resembling team sports that can be practiced under any environmental condition, such as during the COVID-19 pandemic, are deemed crucial for sustaining and improving human mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the American College of Sports Medicine indicates that nearly 35% of elite athletes suffer from psychological issues (disordered eating, burnout, depression, or anxiety) [ 3 ]. Previous studies reported that almost 17.2%–31% of student-athletes had moderate to severe symptoms of stress and anxiety [ 4 , 5 ]. Another study in Canada noticed the prevalence of depressive and anxiety symptoms in athletes by 37.9% and 24.9% of the participants, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%